2022
DOI: 10.34172/jech.2022.14
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sleep Quality and Falls Among Elderly People in Amirkola, Northern of Iran

Abstract: Background: Aging is considered a biological, natural, and inevitable phenomenon that is associated with common problems of sleep quality and falls. The aim of this study was to evaluate the relationship between sleep quality and falls among the elders of Amirkola. Methods: In this case-control study, 250 elders, who were exposed to the falling, and 500 people without the previous falling were randomly selected during 2016-2017. The data were collected according to demographic and Pittsburgh Sleep Quality Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The results of Hornyak et al showed that the amount of fear is negatively and significantly associated with daily activities (5). Fear of falling can lead to the disruption of activity, inactivity, and dependence on performance (10).…”
Section: Introductionmentioning
confidence: 99%
“…The results of Hornyak et al showed that the amount of fear is negatively and significantly associated with daily activities (5). Fear of falling can lead to the disruption of activity, inactivity, and dependence on performance (10).…”
Section: Introductionmentioning
confidence: 99%